Penentuan Penerima BSM Secara Objektiv Berdasarkan Metode Decision Support System VIKOR - Tundo, Tundo; Akbar, Riolandi; Nugroho, Agung Yuliyanto; Saidah, Andi (Universitas Wahid Hasyim, 2024)
This research was conducted because of complaints from several parents regarding the BSM decision at SDN Kalanganyar ABC, however there were several students who were less well off because the choice of BSM was still subjective. SDN Kalanganyar ABC always holds activities related to BSM admissions once a year. It is hoped that this activity can also provide benefits for students who are poor but have excellent grades so they can carry out activities without being burdened by financial needs. In reality, there are still many students who do not receive BSM, even though according to the requirements, these students should be entitled to receive BSM. Therefore, there is a very irrational subjectivity in the ongoing elections. To overcome this problem, researchers tried to develop an application that applies the Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method, namely a method that makes decisions based on a rational compromise of criteria. These criteria include student reports, parents' income, academic achievement, dependents, home conditions, parents' relatives, and activity. From the results of the analysis and application of the VIKOR decision support system, subjective results were obtained for students whose evaluation standards and final decisions were lower than several other students, but the school provided BSM recommendations. To prevent the recurrence of this incident, VIKOR was able to answer objective findings with results of 76.57% with subjective findings of 23.43% in the previous system.